Differences between Students of two Different Study Programs in Assessment of Water Sports Teaching Standard - Bor Oreb; Nikola Prlenda; Goran Oreb (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
The aim of the research was to determine if there was a difference in assessment of pedagogical-material standard in Water sports teaching between students of the Old study program in the period from year 2001 to year 2007 and students of the New (Bologna) study program in the period from year 2010 to 2015. The research was conducted on 2400 students, of which 1797 student entered the sample. Students have assessed 12 variables on a five-grade Lickert type scale through anonymous questionnaire. Variables of assessment were traveling, accommodation, food, teachers, assistants, vessels, climate and curricula for sailing, windsurfing, rowing and kayaking. The results of the arithmetic means for each variable were more positive for students in the new study program. Total arithmetic mean for the Old study program was 4.15, and for the New study program it was 4.46. Based on the results acquired it is determined that there is a difference in assessment between the students of the Old study program and the students of the New study program.